Identification of CRTH2 as a New PPARγ-Target Gene in T Cells Suggested CRTH2 Dependent Conversion of Th2 Cells as Therapeutic Concept in COVID-19 Infection - Becker A; Röhrich K; Leske A; Heinicke U; Knape T; Kannt A; Trümper V; Sohn K; Wilken-Schmitz A; Neb H; Adam EH; Laux V; et al. (ImmunoTargets and Therapy)
Antonia Becker,1 Karoline Röhrich,1 Amanda Leske,1 Ulrike Heinicke,1 Tilo Knape,2 Aimo Kannt,2,3 Verena Trümper,4 Kai Sohn,5 Annett Wilken-Schmitz,1 Holger Neb,1 Elisabeth H Adam,1 Volker Laux,2 Michael J Parnham,2 Valerie Onasch,4 Andreas Weigert,4 Kai Zacharowski,1,2 Andreas von Knethen1 1Goethe University Frankfurt, Department of Anaesthesiology, Intensive Care Medicine, and Pain Therapy, University Hospital Frankfurt, Frankfurt, 60590, Germany; 2Fraunhofer Institute for Translational Medicine and Pharmacology ITMP, Frankfurt, 60596, Germany; 3Institute of Clinical Pharmacology, Goethe University, Frankfurt, 60590, Germany; 4Institute of Biochemistry I, Faculty of Medicine, Goethe-University Frankfurt, Frankfurt, 60590, Germany; 5Innovation Field in-vitro Diagnostics, Fraunhofer Institute for Interfacial Engineering and Biotechnology IGB, Stuttgart, 70569, GermanyCorrespondence: Andreas von Knethen, Email andreas.vonknethen@ukffm.deBackground: COVID-19 is a serious viral infection, which is often associated with a lethal outcome. Therefore, understanding mechanisms, which affect the immune response during SARS-CoV2 infection, are important.Methods: To address this, we determined the number of T cells in peripheral blood derived from intensive care COVID-19 patients. Based on our previous studies, evaluating PPARγ-dependent T cell apoptosis in sepsis patients, we monitored PPARγ expression. We performed a next generation sequencing approach to identify putative PPARγ-target genes in Jurkat T cells and used a PPARγ transactivation assay in HEK293T cells. Finally, we translated these data to primary T cells derived from healthy donors.Results: A significantly reduced count of total CD3+ T lymphocytes and the CD4+ and CD8+ subpopulations was observed. Also, the numbers of anti-inflammatory, resolutive Th 2 cells and FoxP3-positive regulatory T cells (Treg) were decreased. We observed an augmented PPARγ expression in CD4+ T cells of intensive care COVID-19 patients. Adapted from a next generation sequencing approach in Jurkat T cells, we found the chemoattractant receptor‐homologous molecule expressed on T helper type 2 cells (CRTH2) as one gene regulated by PPARγ in T cells. This Th 2 marker is a receptor for prostaglandin D and its metabolic degradation product 15-deoxy-∆12,14-prostaglandin J2 (15d-PGJ2), an established endogenous PPARγ agonist. In line, we observed an increased PPARγ transactivation in response to 15d-PGJ2 treatment in HEK293T cells overexpressing CRTH2. Translating these data to primary T cells, we found that Th 2 differentiation was associated with an increased expression of CRTH2. Interestingly, these CRTH2+ T cells were prone to apoptosis.Conclusion: These mechanistic data suggest an involvement of PPARγ in Th 2 differentiation and T cell depletion in COVID-19 patients.Keywords: Treg, PPARγ, Th 2, COVID-19, NGS, IL-4, CRTH2, FoxP3